Internalized psychopathology dimensions in middle childhood: Cross-sectional and temporal associations. (December 2020) - Cervin, Matti; Pozza, Andrea; Barcaccia, Barbara; Dèttore, Davide
Highlights: Dimensional approaches to child psychopathology can support preventive strategies. We studied network/temporal links of internalising dimensions in community children. General anxiety was most important to the development of other symptoms over time. Prevention may be improved by directly screening for and targeting general anxiety. Abstract: Background: Anxiety, depression, and obsessive-compulsive symptoms often onset during middle childhood and are major causes of disability in young individuals. A better understanding of how these symptoms are linked and unfold over time is important to develop valid etiological models and effective prevention and treatment. Methods: In the present study, 950 community children (8–14 years) reported on a broad range of internalised symptoms at three time points over the course of a year. First, factor analysis was used to examine the overarching dimensions of these symptoms. Second, network analysis was used to examine unique cross-sectional associations among these empirically supported symptom dimensions. Last, longitudinal structural equation models (SEMs) were used to examine temporal associations among the symptom dimensions. Results: Six broad symptom dimensions fitted the self-report data well at all time points. These dimensions were conceptualized as depression, general anxiety, situational fears, compulsivity, intrusive thoughts, and somatic anxiety. Network analysis showed that these dimensions formed a highly interconnected network with general anxiety and somatic anxiety being most central (i.e., most strongly associated with other dimensions) at all time points. Longitudinal SEMs supported the central role played by general anxiety in the temporal associations among these dimensions. Conclusions: Overarching expressions of internalized psychopathology are highly interconnected in middle childhood with possible central roles played by general and somatic anxiety. Interventions aimed at a general proneness for anxiety may be warranted in preventing and treating internalizing symptoms in middle childhood.